Ovalbumin‐specific IgE/IgG4 ratio might improve the prediction of cooked and uncooked egg tolerance development in egg‐allergic children. Issue 4 (April 2014) - Vazquez‐Ortiz, M.; Pascal, M.; Jiménez‐Feijoo, R.; Lozano, J.; Giner, M. T.; Alsina, L.; Martín‐Mateos, M. A.; Plaza, A. M.
Summary Background Accurate predictors of natural tolerance development to cooked and uncooked egg are needed in egg‐allergic patients. Objective To compare the diagnostic performance of different immunological tests in relation to egg allergy versus tolerance. Methods Children aged 5–18 years diagnosed with IgE‐mediated egg allergy were prospectively recruited. All followed an egg‐free diet. Prick test and specific IgE (sIgE) to ovalbumin, ovomucoid and egg white, ovalbumin‐sIgG4 and ovomucoid‐sIgG4 were determined. By boiled and raw egg challenges, children were classified as cooked egg allergic (CEA, n = 50) or tolerant (CET, n = 35), and uncooked egg allergic (UEA, n = 64) or tolerant (UET, n = 21). Statistics. Comparative analysis (CEA vs. CET and UEA vs. UET). Multivariate logistic regression. Partial receiver operating characteristic curve analysis of tests in relation to CEA and UEA. Negative decision points were defined as cut‐offs with sensitivity 95%. Results Ovalbumin‐sIgG4 resulted an independent protective factor for uncooked egg allergy. To identify patients with high probability of egg tolerance, ovalbumin‐sIgE/sIgG4 tended to perform better than sIgE and prick, specifically in children with ovalbumin‐sIgE < 1.9 kU/L (for UEA) and ovomucoid‐sIgE < 2.12 kU/L (for CEA). The most accurate cut‐offs to recommend challenges were ovalbumin‐sIgE/sIgG4 below 2.49 for cooked egg and 1.45 for uncooked egg, which associated 89.5% and 80% probability of tolerance (negative likelihood ratios 0.08 and 0.06), respectively. These cut‐offs identified correctly as tolerant an additional 23% and 14% of children with negative challenges to cooked and uncooked egg, respectively, in comparison with sIgE negative decision points. Additionally, prick test tended to perform better than sIgE alone in predicting cooked and uncooked egg tolerance for ovomucoid‐sIgE < 0.92 kU/L and ovalbumin‐sIgE < 1.37 kU/L, respectively. Conclusions Ovalbumin‐specific IgG4 is an independent predictor of tolerance development to uncooked egg. Ovalbumin‐sIgE/sIgG4 ratio, followed by skin prick test (SPT), seems to perform better than sIgE in identifying egg‐allergic children with high probability of tolerance to cooked and uncooked egg over follow‐up.